Interval training for maximum endurance (VO2max) development
This study attempted to determine which training set would best stimulate maximum endurance development. The following sets of repetition swimming with an intensity that taxed 100% of VO2max were compared to continuous swimming at the same intensity: 20 x 100 m with 30 sec rest; 20 x 100 m with 60 sec rest; 10 x 200 m with 30 sec rest; and 10 x 200 m with 60 sec rest. The stimulation of maximum aerobic capacity can be achieved by swimming: 10 x 200 m with 60 sec rest at 96% of 400 m pace; 6 x 200 m with 30 sec rest at 96% of 400 m pace; and 20 x 100 m with 15-30 sec rest at 95% of 200 m pace.